KEPATUHAN INDONESIA TERHADAP REZIM PARIS AGREEMENT MELALUI PENERAPAN TARGET NATIONALLY DETERMINED CONTRIBUTION DI SEKTOR ENERGI BARU TERBARUKAN PADA ERA KEPEMIMPINAN PRESIDEN JOKO WIDODO - Deni Permana Putra, (2024)
This research explain Indonesia compliance with the Paris Agreement regime through the implementation of new and renewable energy policies consisting of outputs, outcomes and impact variables during President Joko Widodo era, as a form of commitment to the ratification of the agreement that has been established. The purpose of this research to analyze Indonesia compliance in implementing Nationally Determined Contribution target in new and renewable energy sector in national energy mix. Research was conducted using descriptive qualitative methods consisting of primary data sources and secondary data sources. The research data collection techniques used were interviews and literature study. The research was conducted using descriptive qualitative methods using three steps of data analysis, like data collection, data presentation, verification and conclusion. The final result of this research show that Indonesia compliance with the Paris Agreement regime in NDC program in new and renewable energy sector during of President Joko Widodo era has not been implemented optimally. Based on the existence of indicator from research find which show that the principles of 'sustainability' contained in the Paris Agreement has not yet been able by Indonesia.